Amino acids and muscle protein metabolism with aging - Satoshi Fujita, (Penerbit UKM, 2009)
Sarcopenia is age-associated loss of skeletal muscle mass and strength which develops slowly over decades and becomes a significant factor to disability among the elderly population. Although several mechanisms of sarcopenia have been proposed, they all seem to affect the balance between muscle protein synthesis and breakdown, resulting in the net muscle loss. In present article, the most recent findings regarding the role of nutritional intake on muscle protein metabolism in the elderly will be reviewed. Particular focus will be given to dietary protein requirement for elderly, acute anabolic response of amino acids and protein intake, age-associated changes in the response of muscle protein to a meal intake, and the role of insulin resistance of muscle protein metabolism among the elderly. Finally, possible benefits and risks of protein and amino acid supplements for the prevention and treatment of sarcopenia will also be reviewed.